Exploring Gamification with Personality Badges in Software Quality Education - Oliveira, Lauana Maria Cartaxo de; Sousa, Francisco Wilkinis Pereira de; Freitas, Thiago Torres de; Sousa Neto, Deusdedit Teixeira de; Rodrigues, Maria Elanne Mendes; Marques, Anna Beatriz (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
Gamification combines game elements in non-game contexts, enabling its use in education to motivate and engage students in activities. This paper reports on using gamification in teaching Software Quality through two experiences. The first experience was specific to teaching the MPS.BR framework. Based on the results, the second experience encompassed the entire content of a Software Quality course. The gamification strategy adopted involved creating and using badges themed with researchers who contributed to the field of Software Quality in Brazil. These badges were distributed as rewards for completed activities. The Design Thinking (DT) approach was used to create the badges. Data was collected using the Intrinsic Motivation Inventory (IMI) questionnaire to investigate the impact of badge use on student motivation and data on student satisfaction with gamification elements. The results show a positive student reception towards gamification. The implementation of gamification provided satisfactory results in student performance and engagement in activities. Incorporating gamification elements, such as a sticker album for collecting badges, point exchange rules, exercises, and researcher-themed badges, reinforces that the gamification strategy implemented has positive impacts. The predominance of positive responses in both experiences highlights the effectiveness of these elements in the gamification strategy, demonstrating their potential to engage and motivate students.